36,000 Hours of Maintenance Planning on Wartsila Machines W18V50DF Using the Critical Path Method and Evaluation Review Technique Program at PT Antam PLTD - Alfi Taufiq Ramdani; Oviyan Patra; Evan Nugraha (Journal of World Science, 2025)
Antam Diesel Power Plant is one main power plant that supply electricity for processing nickel ore. Antam Diesel Power Plant is consist of 8 engines Wartsila W18V50DF. The reliability of Antam Diesel Power Plant is quietly well maintenance for avoid disturbance in processing nickel ore dan avoid material loss. Obviously, that power plant need frequently maintained, one of maintenance is 36000 hours maintenance. This job is conducted by manufacturer PT Wartsila Indonesia.As contractor Wartsila given a mandatory for shorter the duration of maintenance 36000 hours but still maintain engines performance also avoid loss from both parties. Maintenance Planning 36000 hours using Critical Path Method and Program Evaluation and Review Technique. With using CPM dan PERT the maintainance can be shortened from 36 days to 32 day with increase of margin from 16,75% to 20,91% and probabily of success 77,94%. Using additional crash duration method is not suitable for this project because the cost is increase directly proportional with failure rate and also for avoid labor from being tired.